MYTHOS: A Python Interface for Surface Crystal Structure Prediction of Organic Semiconductors - Lorini, Emilio; Walzer, Karsten; Pfeiffer, Martin; Muccioli, Luca (Journal of chemical information and modeling, 2025)
We introduce a new computational approach for predicting organic crystalline structures on flat surfaces, an essential step in designing and optimizing thin-film systems for electronic devices. Based on molecular mechanics and molecular dynamics simulations, and implemented in a user-friendly Python program, this method enables a sequential layer-by-layer analysis of crystalline formation, thus allowing to identify surface-induced polymorphs (SIPs) and to study the transition between surface and bulk structures. A validation against six diverse test cases demonstrated a good match with experimental crystalline parameters and arrangements, underscoring the reliability of the method in identifying the most relevant polymorphs for a given molecule.